The AI-2/luxS Quorum Sensing System Affects the Growth Characteristics, Biofilm Formation, and Virulence of Haemophilus parasuis - Zhang, Bingzhou (Front Cell Infect Microbiol, 2019)
Haemophilus parasuis (H. parasuis) is a kind of opportunistic pathogen of the upper respiratory tract of piglets. Under certain circumstances, virulent strains can breach the mucosal barrier and enter the bloodstream, causing severe Glässer's disease. Many virulence factors are found to be related to the pathogenicity of H. parasuis strain, but the pathogenic mechanism remains unclear. LuxS/AI-2, as a kind of very important quorum sensing system, affects the growth characteristics, biofilm formation, antibiotic production, virulence, and metabolism of different strains. In order to investigate the effect of luxS/AI-2 quorum sensing system on the virulence of H. parasuis, a deletion mutant strain (ΔluxS) and complemented strain (C-luxS) were constructed and characterized. The results showed that the luxS gene participated in regulating and controlling stress resistance, biofilm formation and virulence. Compared with wild-type strain, ΔluxS strain decreased the production of AI-2 molecules and the tolerance toward oxidative stress and heat shock, and it reduced the abilities of autoagglutination, hemagglutination, and adherence, whereas it increased the abilities to form biofilm in vitro. In vivo experiments showed that ΔluxS strain attenuated its virulence about 10-folds and significantly decreased its tissue burden of bacteria in mice, compared with the wild-type strain. Taken together, the luxS/AI-2 quorum sensing system in H. parasuis not only plays an important role in growth and biofilm formation, but also affects the pathogenicity of H. parasuis.